1988
DOI: 10.1001/jama.1988.03720150031031
|View full text |Cite
|
Sign up to set email alerts
|

Adult T-Cell Leukemia/Lymphoma in Brooklyn

Abstract: Fifteen patients with adult T-cell leukemia/lymphoma (ATLL) were identified in less than a two-year period in the Crown Heights-Bedford Stuyvesant section of Brooklyn, NY. All patients were black; nine patients originated from the Caribbean islands and six from the southern United States. Two of the patients were father and daughter, the first evidence of familial occurrence in the United States. Their clinical course was similar to that of previously described patients with this disorder. To our knowledge, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies have shown that HTLV-1 infection is prevalent in the black, predominantly Caribbean population of central Brooklyn, NY and that ATLL is endemic in this community. [5][6][7] Here we review the clinical and pathologic features of Caribbean ATLL and present our findings in a cohort of ATLL from central Brooklyn, NY. Our data suggest that Caribbean ATLL is not only clinically but also molecularly distinct from Japanese ATLL.…”
mentioning
confidence: 99%
“…Studies have shown that HTLV-1 infection is prevalent in the black, predominantly Caribbean population of central Brooklyn, NY and that ATLL is endemic in this community. [5][6][7] Here we review the clinical and pathologic features of Caribbean ATLL and present our findings in a cohort of ATLL from central Brooklyn, NY. Our data suggest that Caribbean ATLL is not only clinically but also molecularly distinct from Japanese ATLL.…”
mentioning
confidence: 99%